Education System and Network of Quran Memorization Islamic Boarding Schools in Kudus, Surakarta, and Bogor - Zulhannan, Zulhannan; Musyarrofah, Umi (Millah: Journal of Religious Studies, 2024)
This research delves into the education system and network of Quran memorization Islamic boarding schools (also known as pondok pesantren tahfidz Quran in Bahasa Indonesia) in Kudus, Surakarta, and Bogor. The study was conducted in Pondok Pesantren Yanbu’ul Qur’an in Kudus, Ma’had Tahfizhul Qur’an, Yayasan Sosial dan Pendidikan Islam Isy Karima in Surakarta, and Pesantren Terpadu Darul Qur’an Mulia in Bogor. The research methodology employed was a descriptive, analytical, and historical approach integrated and presented through qualitative processes involving data collection through observation, interviews, and document analysis at the three Quran memorization Islamic boarding schools. The data analysis steps include data reduction, data display, and data verification through triangulation. The research findings indicate the uniqueness or characteristics of each Quran memorization Islamic boarding schools. Pondok Pesantren Yanbu’ul Qur’an has the uniqueness of five concepts: sincerity, obedience, compliance, the importance of quality, patience, and meticulousness. Meanwhile, Ma’had Tahfizhul Qur’an, Yayasan Sosial dan Pendidikan Islam Isy Karima required students to complete the recitation of the entire Quran, 30 chapters, within a duration of two years, utilizing visual, audio, and kinesthetic techniques. Pesantren Terpadu Darul Qur’an Mulia features comprehensive interaction in a halaqoh format encompassing techniques such as recitation, comprehension, memorization, and application that nurture noble character. Regarding the inevitability of the network, the research emphasizes that the Quran memorization Islamic boarding schools serves as a focal point for the community. Although exclusively owned by the kyai (Muslim leader), these Quran memorization Islamic boarding schools remain a possession of the broader community, with a self-reliant management system independent of specific government or non-governmental organizations.